KAJIAN PAKET TEKNOLOGI BAWANG MERAH DI HARANGGAOL SUMATERA UTARA - Loso Winarto; M. Prama Yufdy; Lermansius Haloho (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2009)
The Package Technology of Red Onion in Haranggaol, North Sumatera. The cultivation of red onion around Toba Lake has not been developed well due to pest and disease problems, improper cultivation practices adopted by farmers as characterized by the planting local varieties. A study was conducted in Haranggaol, North Sumatra in an effort to introduce suitable technology needed for increasing production. Two high yield varieties `Tiron' and Thilipina' were planted using two recommended technology packages which were then compared to local practices. Research results indicated that Tiron produced the highest number of tiller i.e. 17.30/cluster, while Philipina yielded the highest production (20.51 t/ha) with larger size of bulb (141 bulb/kg). In comparison, Tiron produced 7.88 t/ha with higher number of bulb at 237 bulb/kg while local variety produced 7.43 t/ha with 221 bulb/kg. The highest reduction of bulb weight after 60 days stored was Philipina reached 20.40%, Tiron 19.20% and local variety 18.80%. The control of Spodoptera exiqua by using feromonexi showed that 1,059 heads of imago could be trapped. If one pair of imago can produced 500-600 eggs, it can be estimated that this treatment could kill 635,400 larvas of Spodopthera exigua. Results also indicated that the package technology 2 with Philipina showed R/C at 2.8, followed by package technology 1 with Tiron variety at 1.7 and local practice at 1.2 Key words: Red onion, technology package, varietyPertanaman bawang merah di sekitar kawasan Danau Toba tidak berkembang bahkan cenderung menurun akibat serangan hama dan penyakit, budidaya yang masih tradisional dan belum digunakannya varietas unggul. Berkaitan dengan hal tersebut, telah dilakukan suatu pengkajian perbaikan budidaya dan varietas unggul bawang merah di Desa Haranggaol, Kecamatan Haranggaol Horisan, Kabupaten Simalungun, Sumatera Utara. Teknologi yang diterapkan adalah bawang merah varietas Tiron dan Philipina yang ditanam dengan dua paket teknologi anjuran dibandingkan dengan teknologi petani. Hasil kajian menunjukkan bahwa jumlah anakan tertinggi diperoleh pada varietas Tiron (17,30/ rumpun). Produksi yang tertinggi didapat pada varietas Philipina yaitu 20,51 t/ha dan umbi lebih besar (141 umbi/kg); Tiron 7,88 t/ha dengan jumlah umbi 237/kg sedangkan varietas lokal hanya mencapai 7,43 t/ha dengan jumlah umbi 221/kg. Penyusutan setelah 60 hari dalam penyimpanan tertinggi terdapat pada varietas Philipina mencapai 20,40%, Tiron 19,20% dan Samosir 18,80%. Pengendalian hama spodoptera exigua dengan pemasangan Feromon-exi dapat ditangkap imago jantan sebanyak 1.059 ekor. Jika sepasang imago mampu bertelur 500 — 600 butir maka diperkirakan dapat membunuh larva keturunannya mencapai 635.400 ekor larva Spodoptera exigua. Hasil perhitungan menggunakan R/C secara berturut-turut Teknologi-1 (Bawang Tiron) sebesar 1,7; Teknologi-2 (bawang Philipina) sekitar 2,8 dan Teknologi Petani (Bawang Samosir/Lokal) sebesar 1,2. Kata kunci: Bawang merah, paket teknologi, varietas